KAUM MUDA DALAM ERA PERUBAHAN ZAMAN (Pemikiran Alternatif Kateketis) - Agustinus Supriyadi (Lembaga Penelitian STKIP Widya Yuwana, 2018)
The development of this technology matures more rapidly as human beings who have a high curiosity, each of us must try to do something new. Not a problem if each of us can understand it wisely and use them appropriately and wisely because of all that is demand time we need to know as a human being who has the time and living in the era. There was no denying young people today prefer instant lifestyle and demanding all the good and bad without any struggle. The dynamics of young people living in the various facts presented, including a variety of degeneration. The facts about the slump of moral, intellectual, and spiritual youth is not an absolute thing that can not be changed There are still many roads lead to Rome, so did the rise of young people, there are many ways towards him. Opportunity is still wide open as long as we actually believe and try So much indeed that we must face the challenges before it all come true. Catechesis of young people with a variety of appropriate methods should refer to a formation character useful for the development of self and community and church.